The Teacher's Role as an Applicator of “Profil Pelajar Pancasila” in “Merdeka Belajar” Curriculum - Suliyanah, Suliyanah; Khasanah, Uswatun; Alifia, Dita; Agustinaningrum, Nur Afni; Sabrina, Nadya Mazayu Nur; Deta, Utama Alan (Mitra Edukasi dan Publikasi, 2023)
This research was conducted with the aim of analyzing the teacher's role as an applicator of Pancasila student profiles in the independent curriculum. This research is based on the development of the era which is getting faster which is marked by the development of information technology which triggers the fading of noble values and behavioral deviations in children. Therefore, it is necessary to have character education to foster and guide students to become individuals who behave, behave, and order words well. In the independent curriculum, there is a profile of Pancasila students which is a form of character education. Through the programs, students are expected to be able to apply Pancasila values in their lives. In making it happen, the role of a teacher is needed. This research uses qualitative methods through literature studies and interviews. The data that has been obtained will be processed and then analyzed. From the data that has been obtained, it can be concluded that the teacher has a strategic role in realizing the goals of having a Pancasila student profile. The teacher who is known as someone who is admired and imitated has a role as a role model for students to behave and behave. The teacher is the leader in the class. So that the condition of the teacher in learning can directly affect the condition of students. Teachers are indeed role models for students, but school principals and non-educational staff should also be good examples for students because in realizing a Pancasila student profile that can be applied by students, teachers also need support from all elements of the school.